e-Pocket Musafir: The Development of Android Mobile Apps to Explore Religious Information for Muslim Traveler - Husain, Muhammad Hafiy Aiman; Mohd Hatta Mohamed Ali @ Md Hani,; Dang Sofia Mohd Zahari,; Nur Alisya Nadira Mohd Sukeri, (Multidisciplinary Applied Research and Innovation, 2022)
Musafir (مسافر) is a word in Arabic meaning ‘traveler’ which refers to a person who is on a long journey. Traveling is encourage (sunnah) in Islam for a person to get experience and see the world. Even in a state of traveling, Muslims cannot leave the prayer because the prayer is something that is obligatory as a Muslim. Therefore, Allah SWT has given a privilege or facility to people who travel to perform prayers by performing prayers in the jamak and qasar. But to perform this prayer, muslim who are on a journey must meet the specified conditions which is travel distance is not less than 2 Marhalah (90KM) from the starting point to their destination. Since this way of praying is rarely performed, people who travel should have a reference before performing this prayer, and most references nowadays are in the form of non-interactive documents and are difficult to carry anywhere. Therefore, the project aims to develop a mobile application for Muslim traveler which will guide them to perform Jamak & Qasar prayers. This application is named e-Pocket Musafir. The application will provide some features for Muslims to use such as tasbih, Qasar Jamak prayer guidance, Hadith and prayer times. Therefore, Android Studio as well as Adobe Illustrator will be used to develop the e-Pocket Traveler.